PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MI AL-KIFAYAH PEKANBARU - Khasanah, Niswatul (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Learning outcomes are the results of the learning process to achieve specific goals, so the research aims to improve the mathematics learning outcomes of the fourth-grade students at MI Al-Kifayah Pekanbaru through the application of the Student Facilitator and Explaining Cooperative Learning Model. The research took place from October 30, 2023, to November 10, 2023, with 4 learning sessions and 2 daily quizzes. The subjects in the study are 20 students from MI Al-Kifayah Pekanbaru. The form of the research is classroom action research consisting of two cycles. The data collection technique in the research was conducted using observation techniques and learning outcome tests. The test techniques included daily quizzes I and daily quizzes II. The mathematics learning outcomes of the students were analyzed for student mastery with the average mathematics learning outcomes of the fourth-grade students at MI Al-Kifayah Pekanbaru. The average learning outcome analysis compared the results before and after the intervention.From the comparison results, there is an improvement in the learning outcomes of the 4th-grade students at Damaia Sejahtera Elementary School, Pekanbaru. At the baseline score, the number of students who completed the course was 7 students (35%), in the first daily test the number of students who completed was 11 students (45%), an increase of 5 students, and in the second daily test, the number of students who completed was 16 students (80%). The average student learning outcome at the baseline score was 67.9, in the first daily test it was 76, and in the second daily test, it became 81.65. The above results can be concluded that the application of the cooperative learning model student facilitator and explaining can improve the learning outcomes of 4th-grade students at MI Al-Kifayah Pekanbaru.